Peer effects in pro-social behavior: social norms or social preferences? - Simon Gächter; Daniele Nosenzo; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
We compare social preference and social norm based explanations for peer effects in a threeperson gift-exchange game experiment. In the experiment a principal pays a wage to each of two agents, who then make effort choices sequentially. We find that both agents supply more effort in response to a higher own wage, even though supplying minimal effort maximizes own-earnings. In our baseline treatment we observe that the second agent's effort is influenced by the effort choice of the first agent, even though there are no material spillovers between agents. This peer effect is consistent with inequity aversion and we also show, by conducting an experiment to measure social norms, that it is consistent with social norm compliance. We design a second treatment where social norm compliance, but not inequity aversion, predicts this peer effect. In this treatment we do not observe peer effects. Our results suggest that, in our context, inequity aversion provides a parsimonious explanation for observed peer effects.
Keywords: A13; C92; 330; peer effects; social influence; gift-exchange; experiment; social preferences; inequity aversion; measuring social norms